2011
DOI: 10.1002/anie.201103707
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Responsive Capture and Release of DNA in a Ternary Supramolecular Complex

Abstract: The wavelength determines whether DNA is captured in a light‐responsive ternary supramolecular complex or released (see scheme). The reversible binding of DNA is triggered by a photoisomerization, which switches the complex from a multivalent to a monovalent binding mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
156
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(163 citation statements)
references
References 42 publications
3
156
0
4
Order By: Relevance
“…Azobenzene is unique since it can be readily photo-isomerized as well as form photo-responsive inclusion complex with b-CD via host-guest interaction in water. 40 It was also reported that azobenzene containing dipeptides show a photo-induced change of selfassembly in presence of a-CD. 41 However, to the best of our knowledge, a light-responsive LMWG based on host-guest interaction is so far unprecedented.…”
mentioning
confidence: 94%
“…Azobenzene is unique since it can be readily photo-isomerized as well as form photo-responsive inclusion complex with b-CD via host-guest interaction in water. 40 It was also reported that azobenzene containing dipeptides show a photo-induced change of selfassembly in presence of a-CD. 41 However, to the best of our knowledge, a light-responsive LMWG based on host-guest interaction is so far unprecedented.…”
mentioning
confidence: 94%
“…[3g,7] Therefore, it would be of great interest to develop a highly charged polycation that possesses full transfection capacity and membrane activity during the course of gene transfer, but can be triggered to transform to a less charged or uncharged material with low membrane activity post-transfection, such that intracellular DNA unpackaging can be facilitated and toxicity can be reduced. [8] …”
mentioning
confidence: 99%
“…It involves caging the molecules of interest by a photo-cleavable molecule or bond, which can then be cleaved by light irradiation and thus release the caged molecules to function [68]. Various molecules, such as proteins, peptides, nucleic acids, amino acids, and drugs, have been photocaged and delivered to the cells/animals followed by targeted photolysis at the area of interest, thus enabling the activation of these molecules with a high spatiotemporal resolution [611]. …”
Section: Introductionmentioning
confidence: 99%
“…Upon UV light irradiation, azo-benzene molecules are isomerized from their thermodynamically stable trans -state into their metastable cis -state, thereby inhibiting their host–guest interactions with cyclodextrin due to changes in polarity and steric hindrance [14,15]. This unique characteristic provides photoswitchable control over the azobenzene–cyclodextrin host–guest complex, which has been explored for a broad range of applications, including light-responsive hydrogels [16,17], micelles [11], vesicles [18], and other drug delivery vehicles [19]. However, similar to most photocaging systems, the trans -to- cis photoisomerization of azobenzene requires UV light activation, which is harmful to biological systems [13].…”
Section: Introductionmentioning
confidence: 99%